Pengaruh Rasa Syukur terhadap Kesejahteraan Psikologis pada Mahasiswa S1 UIN Tulung Agung di Masa Pandemi Covid-19 - Fatmala, Dzakiyyah; Sari, Citra Ayu Kumala (Journal of Islamic and Contemporary Psychology, 2022)
The Covid-19 pandemic that lasted for more than one year affected the psychological well-being of the community, including students. This study aimed to determine the effect of gratitude on psychological well-being in college students during the Covid-19 pandemic. The method used in this study is a quantitative method with data analysis techniques in the form of simple linear regression analysis. The population in this study amounted to 20,989 people, with total sample of 267 people, used cluster random sampling technique. The data collection technique used the Gratitude Scale and the Psychological well-being Scale. The results show that the significance value = 0.000 <0.05 so that H0 was rejected with the regression equation Y = 20.236 + 1.243x. There is an effect of gratitude on psychological well-being in undergraduate students of Universitas Islam Negeri (UIN) Tulungagung during the Covid-19 pandemic. Moreover, gratitude has on effects the psychological well-being of 26.7% of undergraduate students of UIN Tulungagung during the Covid-19 pandemic, and the remaining 73.3% are other factors.